Solution-Based Processing of Optoelectronically Active Indium Selenide - Kang, Joohoon; Wells, Spencer A; Sangwan, Vinod K; Lam, David; Liu, Xiaolong; Luxa, Jan; Sofer, Zdeněk; Hersam, Mark C (Advanced materials (Deerfield Beach, Fla.), 2018)
Layered indium selenide (InSe) presents unique properties for high-performance electronic and optoelectronic device applications. However, efforts to process InSe using traditional liquid phase exfoliation methods based on surfactant-assisted aqueous dispersions or organic solvents with high boiling points compromise electronic properties due to residual surface contamination and chemical degradation. Here, these limitations are overcome by utilizing a surfactant-free, low boiling point, deoxygenated cosolvent system. The resulting InSe flakes and thin films possess minimal processing residues and are structurally and chemically pristine. When employed in photodetectors, individual InSe nanosheets exhibit a maximum photoresponsivity of ≈5 × 107 A W-1 , which is the highest value of any solution-processed monolithic semiconductor to date. Furthermore, the surfactant-free cosolvent system not only stabilizes InSe dispersions but is also amenable to the assembly of electronically percolating InSe flake arrays without posttreatment, which enables the realization of ultrahigh performance thin-film photodetectors. This surfactant-free, deoxygenated cosolvent approach can be generalized to other layered materials, thereby presenting additional opportunities for solution-processed thin-film electronic and optoelectronic technologies.
Keywords: photodetectors; cosolvent; 2D materials; liquid phase exfoliation; surfactant-free; deoxygenated